Forming the Research Component of the U.S. Defense Budget Policy - A. V. Balyshev; V. I. Konnov (Vestnik MGIMO-Universiteta)
The authors examine the structure and principles of the defense spending for research and development in the U.S., as well as the main agencies and contractors involved. The article offers specific cases to illustrate the role of key players of the U.S. budgetary process, the U.S. President, Congress, Department of Defense, and their relations with the scientific community. Spending in this area is organized as a three-level structure, which includes development of new weapons systems, creation of military platforms and systemic integration of the armed forces. One of the most noteworthy participants on the weapons development level is the Defense advanced research projects agency (DARPA), which provides support for R&D projects able to facilitate technological breakthroughs and provide results applicable by the armed forces. The emphasis of the article is on the participation of the private sector on all levels of the defense spending and especially in the systemic integration. At this level even formulating the request becomes a highly challenging task, which demands involvement of the most highly qualified specialists and organizations. The authors analyze the advantages and disadvantages of the wide participation of commercial enterprises and provide cases illustrating possible conflicts between government and private actors and ways of their resolution.